Wind-Borne Transmission of Infectious Laryngotracheitis Between Commercial Poultry Operations - Johnson, Y.J.; Gedamu, N.; Colby, M.M.; Myint, M.S.; Steele, S.E.; Salem, M.; Tablante, N.L (International Journal of Poultry Science, 2005)
Infectious Laryngotracheitis (ILT) is an acute respiratory disease of poultry and causes significant economic losses due to increased mortality and decreased productivity. First described in 1925, ILT has been extensively studied, but little is known about the epidemiology of the disease. In the past 15 years, there have been severe ILT outbreaks in several poultry-producing states. The spread of ILT in outbreak situations is typically quite rapid, and then in an ever-widening arc around the initial case. The mechanism of this spread is not well understood, and many hypotheses are currently in existence. Several risk factors that have been identified are indicative of wind-borne transmission. A case-control study of 18 case and 122 control flocks was conducted. A GIS database of poultry operations and meteorological data from local weather stations were employed to analyze the risk of clinical ILT associated with prevailing wind patterns. Case farms were 9.9 times more likely located within the wind vector of a clinical ILT flock during the 14 day incubation period for ILT than control flocks (p< 0.001). House orientation and proximity to a backyard flock or a commercial flock were not significantly associated with case status. The control-to-case flock distance was significantly greater than the case-to-case flock distance (p=0.03). House ventilation system, wind vector, and distance from another case flock were presented to a backward eliminating logistic regression model. Only wind vector variable was retained in the model. The point estimate for the odds ratio was 0.110 (95% confidence interval 0.038 - 0.322).